INTERNET ACCESS AS A FUNDAMENTAL RIGHT (Reflection and Critique Law Magazine, 2022)
The objective of this research was to identify the need to elevate internet access to a fundamental right. For this, the bibliographic method was chosen, which allowed us to demonstrate that, according to the International Telecommunication Union (2019), un agency, 49% of the world's population does not yet have access to the Internet, in addition to the risk of violation of rights such as privacy for those who have a connection. From a legal point of view, definitions of fundamental rights and their respective generations and constitutional provisions on the subject were presented. An exercise has also been done to verify that internet access is a fundamental right. In addition, research has shown that internet access can be seen as a fundamental guarantee, that is, as a means of exercising other rights. Thus, it was concluded that internet access should be classified as a fundamental right, with the aim of generating state initiatives that increase access to the network while protecting the rights of those who access it.